Cardiac-specific deletion of voltage dependent anion channel 2 leads to dilated cardiomyopathy by altering calcium homeostasis - Thirupura S. Shankar (Nature Portfolio, 2021)
The authors found that VDAC2 plays a crucial role in influencing mitochondrial calcium dynamics and cellular calcium signalling. A VDAC2 agonist, efsevin, rescued the heart failure phenotype, identifying a new potential therapeutic target for heart failure.